Tyrosine residues at the immunoglobulin-C-type lectin inter-domain boundary of intimin are not involved in Tir-binding but implicated in colonisation of the host - Simmons, Cameron (2018)
Intimin is an outer membrane adhesion molecule involved in bacterial adhesion to intestinal epithelium by several human and animal enteric pathogens, including enteropathogenic and enterohaemorrhagic Escherichia coli and Citrobacter rodentium. Intimin binds to the translocated intimin receptor, Tir, which is delivered to the plasma membrane of the host cell by a type III protein translocation system. Intimin is also implicated in binding to a host cell-encoded intimin receptor (Hir). The receptor-binding activity of intimin resides within the carboxy terminus 280 amino acids (Int280) of the polypeptide. Structural analysis of this region revealed two immunoglobulin-like domains, the second of which forms a number of contacts with the distal C-type lectin-like module. Specific orientation differences at this inter-domain boundary, which consists of several tyrosine residues, were detected between the crystal and solution structures. In this study, we determined the influence of site-directed mutagenesis of each of four tyrosine residues on intimin-Tir interactions and on intimin-mediated intimate attachment. The mutant intimins were also studied using a variety of in vitro and in vivo infection models. The results show that three of the four Tyr, although not essential for A/E lesion formation in vitro, are required for efficient colonisation of the mouse host following oral challenge.